Establishing a marine conservation baseline for the insular Caribbean. (October 2015) - Knowles, John E.; Doyle, Emma; Schill, Steven R.; Roth, Lynnette M.; Milam, Amy; Raber, George T.
Abstract: Marine protected areas are a primary strategy for the conservation of marine habitats and species across the globe. In small island developing states, they often exceed their terrestrial counterparts in both number and area. To assess their effectiveness as a conservation measure over time, the accurate and up-to-date representation of marine protected areas through spatial and tabular data is imperative in order to establish baselines. Various regional and global agreements have set specific protection targets and these require spatial reporting on protected areas as an indicator of progress. For the insular Caribbean region, this study considers progress towards global Aichi Target 11 of the Convention on Biological Diversity which is to conserve at least 10% of coastal and marine areas, and progress towards the regional target of the Caribbean Challenge Initiative (CCI) to protect "at least 20% of nearshore marine and coastal habitats", both aiming for a 2020 deadline. Progress towards these targets differs widely depending on the accuracy of the datasets and the methods used. In an effort to update the current baseline of protection within the insular Caribbean, multiple governments, the Nature Conservancy and the Caribbean Marine Protected Area Management Network and Forum collaborated to develop a single insular Caribbean protected area dataset with accurate boundary information and the best available ecoregional and political boundaries. This study represents the most in-depth and spatially accurate effort to date to determine marine protected area coverage in the insular Caribbean. It is found that some form of marine management has been designated for around 7.1% of our study area in the insular Caribbean; progress towards Aichi Target 11 averaged among sovereign states within the insular Caribbean stands at approximately 3.25% and only three of the 10 participating governments in the CCI have reached their 20% target. Ocean protection was further assessed across the 25 governments and the three marine ecoregions by four different marine zones. Recommendations are made on regional to global cooperation for data sharing and reporting on indicators, highlighting possible directions to fill marine conservation gaps in the insular Caribbean. highlights: A single insular Caribbean protected area dataset with accurate boundary information was developed. MPA coverage across the insular Caribbean is not far behind global reference values. The insular Caribbean has a large number of small MPAs. Large MPAs greatly influence the protected area coverage targets.